2019
DOI: 10.1039/c8ra10584g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the role of interfacial water on the tribology between graphite and metals

Abstract: We investigated the role of interfacial water on the atomic-scale tribology of graphite by contact atomic force microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In this case, too, we attribute the adhesion to capillary effects but explain the larger measured adhesion force value compared to SiO x vs. graphene based on the larger Au-tip radius R tip . In agreement with our previous results, we set R tip = 25 nm for Au-and Pt-tips [5,43]. For the SiO x -tip, we set R tip = 7 nm in agreement with the manufacturer's data.…”
Section: Resultssupporting
confidence: 58%
“…In this case, too, we attribute the adhesion to capillary effects but explain the larger measured adhesion force value compared to SiO x vs. graphene based on the larger Au-tip radius R tip . In agreement with our previous results, we set R tip = 25 nm for Au-and Pt-tips [5,43]. For the SiO x -tip, we set R tip = 7 nm in agreement with the manufacturer's data.…”
Section: Resultssupporting
confidence: 58%
“…The observed increase effective stiffness with the normal load raises questions regarding its origin. FFM measurements and molecular dynamics simulations on graphene/ graphite and metals in the presence of water surroundings concluded that at high normal loads the water had insignificant effect of friction [58,72]; however, the presence of water was shown to affect the load-dependent friction hysteresis on graphene [39]. Yet, the question whether this effect is specific to the system measured here or may be of more general nature for the interaction between other non-polar liquids with ionic crystals requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Graphite has been used extensively as a lubricant highlighting its capacity to wear resistance between surfaces. This is partially due to the delocalized electrons associated with graphite, coupled with 'aromatic stabilization' (where specific carbon compounds are arranged in energetically favourable conformations that resist change) [48,49].…”
Section: (B) Graphitementioning
confidence: 99%